Research results of biological resources and and biodiversity of Vietnam sea: current status, treats, proposed solutions to use lasting - Do Cong, Thung (Vietnam Journal of Marine Science and Technology, 2022)
The marine biology investigation and research activities in our country since 1990 have made remarkable changes; especially there have been changes in thinking, scale, content, level, research, skills research, and international relations in research. We have proactively overcome the limitation of general, preliminary, and undirected investigation to shift to new thinking about research gradually. Research on changes in typical ecosystems is extended to the whole sea, to deep water, offshore and remote islands such as Pracel (Hoang Sa) and Spratly (Truong Sa). We have focused on researching issues about the causes of formation, the law of fluctuations, and the mechanism of action of marine processes, studying the basis of the application of technology, and creating new technologies to solve these problems in practice. Therefore, there have been outstanding results compared to the period before 1990. It has been identified that there is a high level of biodiversity in the sea of Vietnam with over 11,000 species, forecast to reach 12,000 marine species, and 134 species are listed in the Red Book of Vietnam, but the structure of biodiversity and marine resources in our country are also susceptible and vulnerable. Also, nearly 20 specific ecological systems and sub-systems have been identified in the sea and coastal areas; Seafood reserves of almost 4 million tons are an essential basis for developing eco-tourism, fishing, and aquaculture. Due to economic and social activities, many threats to marine biodiversity have been caused: narrowing of ecosystem area, decrease in density, number of species and reserves, decrease in ecosystem value, and habitat degradation. The real solutions to conserve and sustainably use biodiversity and marine resources include institutional and policy solutions, strengthening the construction of protected areas, artificial reefs, and areas where exploitation is prohibited over time, sustainable exploitation and cultivation of marine resources, and sustainable marine economic development.